The roots of gender bias: misogynist hadiths in pesantrens - Marhumah Marhumah (IAIN Salatiga, 2015)
Women are regarded as “the second class” by some people in pesantrens. Thisknowledge has rooted in hadiths cited in the books studied and implementedin many pesantrens. To counteract this tendency, it is therefore important touse a feminist approach to review and criticize the books which can also beused to understand and solve the problems of mis-interpretation of religioustexts. The misogynist hadiths have been widely circulated and taught in pesantrenunder the authority of Kyai (male religious clerics) and nyai (female religiouscleric) who have the authority to decide which hadiths are allowed to betaught and socialized in religious teachings and sermons. This is because manyteachers emphasize the importance of preserving tradition and religious normsdisegarding gender bias. Some feminist activists have tried to reform the mindsetsof pesantren leaders both male and female by changing the authoritarian modelof leadership to a democractic one. To do this, new historical, sociologicaland anthropological approaches are required to re-interpret and contextualizemisogynist hadiths.Perempuan dianggap sebagai warga “kelas dua” dalam beberapa kitab yangdiajarkan di pesantren. Pengetahuan ini memiliki akar yang kuat dalam hadith-hadith yang dikutip dalam buku-buku yang diajarkan di pesantren. Untuk melawan arus kecenderungan ini, penting untuk menggunakan pendekatanfeminis dengan meninjau kembali dan mengkritik kitab-kitab tersebut.Pendekatan ini dapat digunakan sebagai cara untuk memahami dan menyelesai-kan masalah kesalahan tafsir pada teks teks keagamaan. Hadith-hadits misoginis(membenci perempuan) diajarkan secara luas di pesantren di bawah wewenangPak Kyai atau Ibu Nyai yang menentukan kitab-kitab mana yang boleh dandilarang di pesantren. Para guru tersebut lebih mementingkan menjaga tradisidan norma-norma agama yang seringkali bias jender. Beberapa aktivis feministelah mencoba mereformasi pola pikir para pengasuh pesantren baik lakimaupun perempuan dari kepemimpinan yang otoriter ke kepemimpinan yangdemokratis. Untuk itu, pendekatan-pendekatan historis, sosiologis danantropologis yang baru diperlukan guna memahami ulang hadith-hadithmisoginis tersebut.